(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
The current approach to managing menopause and perimenopause is based on an individual basis. Menopausal hormone therapy (MHT) is still the best treatment for symptoms, but its use depends on a thorough evaluation of the patient’s medical background. Clinical guidelines support MHT for healthy people under 60 or in the first ten years after menopause, as long as the therapeutic advantages are thought to outweigh any possible risks. Furthermore, there are numerous effective lifestyle-based and non-hormonal interventions available as substitutes, such as pharmaceuticals and therapeutic approaches. The main goal is still to work together to develop a treatment plan for managing symptoms and fostering long-term physiological health. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S16]